(untitled) (Research, Society and Development, 2022)
The role of a professional nutritionist in oncology sectors is to contribute to the recovery and maintenance of the patient’s nutritional status, nutritional counseling and intervention before and during treatment are indispensable factors in this process. The objective of this study was to evaluate the nutritional status and adequacy of food intake of patients with cancer at a public hospital in Aracaju SE. The research included cancer patients, adults and elderly, of both sexes. Measures of weight, height, arm circumference, triceps skinfold were collected, in addition to the 24-hour dietary recall. Of the total number of individuals evaluated, women were the majority 74.3% (n=124) and had higher cases of alterations in their nutritional status. Breast cancer appears as the largest number of cases, 35.3% (n = 59), of the treatments used in chemotherapy for the greatest use, 53.9% (n = 90). Regarding food consumption, potassium, calcium, iron (51-70), magnesium, sodium (31-50) and vitamins A, D, E, B1, B6 (51-70) and B9 were below the appropriate recommendation for according to the Dietary Reference Intakes (DRIs).: Results were found for greater weight loss in women in addition to an inadequacy of micronutrients, requiring nutritional monitoring to stabilize or minimize these changes.